Comparative cleaning tests with modified protein and starch residues. (June 2016) - Otto, C.; Zahn, S.; Hauschild, M.; Babick, F.; Rohm, H.
Abstract: The cleanability of food contact surfaces is determined by surface characteristics and the properties of the soiling material. Effects of selected physicochemical parameters of biopolymer soils on the removal from stainless steel were studied using a laboratory flow cell system with continuous removal measurement and, additionally, gravimetric detection. The results show the potential for improving cleaning processes on the basis of structural properties of the biopolymers. A higher cleaning efficiency was achieved when surface energy and cationic charge of the polymers was lower, indicating that adhesive interactions (van der Waals forces of attraction and electrostatic forces) between surface and polymer play a dominant role. The effects of pre-heating treatments of the soils, inducing molecular changes, on removal behavior were however not significant. The results indicate that a holistic view of product and process design is useful to develop efficient cleaning protocols. Highlights: Continuous flow cell is useful to classify the removal of modified food components. Biopolymer modification affects soil properties and partly cleaning efficiency. Cleaning efficiency is higher for biopolymers with lower energy and lower cationic charge.